Vitronectin and Its Receptor (Integrin αvβ3) During Bovine Fertilization In Vitro - Thys, Mirjan; Nauwynck, Hans; Vandaele, Leen; Bijttebier, Jo; Maes, Dominiek; Favoreel, Herman; Soom, Ann Van (IntechOpen, 2012)
None